Pengaruh Kepemimpinan Transformasional dan Transaksional pada Kinerja Pegawai Bappeda Kota Bandung - Ina Ratnamiasih; Warenih W (TRIKONOMIKA, 2014)
Leadership in government institution increasingly recognized role in improving employee performance. As one of the organizations responsible for performing research and development planning for local development, Bappeda need leaders who are able to use the leadership style. This study aims to look at the effect of transformational and transactional leadership on employee performance Regional Development Planning Board (Bappeda) in Bandung. Data was collected using a census technique on all employees of the Bappeda totaling 88 people. Data were analyzed using Structural equation modeling (PLS). The results showed a positive and significant influence of transformational and transactional leadership on employee performance. Transactional leadership has a greater influence than the transformational leadership. The next study is expected to use different methods in order to more clearly the contribution of leadership on employee performance, especially in government institution.